Determinants of intention to adopt maize drying technologies among small-scale farmers in Kenya - Kariuki, Grace (Graduate School of Business, 2018)
Maize, being the most common staple food across many parts of the world, especially sub-Saharan Africa, is, in most cases, preserved through sun drying techniques among small-scale farmers. This method is prone to significant losses, which could be avoided through the use of mechanised drying technologies. Unfortunately, many farmers in developing countries such as Kenya have yet to adopt this technique on a large scale. It is against this background that this research sought to identify the factors that influence the adoption of mechanised maize drying technologies among small-scale farmers in Kenya. This study was anchored in the Theory of Planned Behaviour (TPB), which offers a structured framework for predicting and explaining human behaviour based on personal attitudes, subjective norms, and perceived behavioural control. Financial constraints and the knowledge base of the farmers were also included in the analysis, as these are important factors in the likelihood of farmers adopting the technology. Data were collected by means of structured interviews with 397 farmers in Nakuru County, Kenya. Correlation analysis was used to determine the strength, magnitude, and significance of the relationships between the variables. Ordered logit, a regression model, was used to determine the relationship between the independent variables, which were: financial resources, personal attitudes, subjective norms, perceived behavioural control and knowledge, and the dependent variable, which was intention to adopt technologies. In addition, other control variables such as gender of the household head, farm size, age of the farmer, educational level of the household head and farm assets owned by the farmer were included as independent variables. The results indicated that 69.02 percent of farmers did not plan to utilise mechanised maize drying technologies, which is cause for concern from a policy perspective. The ordered logit results revealed that all the independent core factors significantly influenced adoption intentions. The farmers’ views related to their perceived behavioural control, and financial constraints negatively influenced their intentions to adopt mechanised maize drying technologies. Among the control variables, farm size and educational level positively influenced the adoption intention, while age had a negative influence. Based on these results, it is evident that there is a need to consider personal attitudes, subjective norms and perceived behavioural control of farmers, as well as the implementation of a nationwide campaign to encourage the adoption of mechanised maize drying techniques and a government strategy to bring the cost of credit down, while also ensuring its availability to small-scale farmers. The campaign will bridge the information gap and enhance adoption of mechanised maize drying technologies.